Pengaruh Perubahan Digitalisasi, Kesenjangan Digital dan Transformasi Terhadap Efektivitas Perusahaan - Septi Lis Anandita; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Mahasiswa Kreatif, 2024)
This study aims to examine the effect of digitalization changes, digital divide, and transformation on the effectiveness of companies in South Jakarta. This research method uses a quantitative approach by collecting data through questionnaires distributed to several employees in South Jakarta. The sampling technique uses purposive sampling method, and the data obtained are analyzed using regression analysis. The results of this study show that changes in digitalization, sausage gaps and transformation significantly affect the effectiveness of existing companies in South Jakarta. In the digital era, which has been applied in several organizations, it brings new changes to increase the effectiveness and productivity of employee performance. This shows that digitalization provides an important point for transformation of company effectiveness. The implication of this research is the importance of companies paying attention to changes in digital-based work systems to reconsider the digital divide in some companies that allow disruption of balance to employee performance, therefore it is necessary to conduct research related to changes in digitalization, digital divide, and transformation of company effectiveness.